Carcinoma of Stomach diagnosed by Trans abdominal Sonography and guided FNAC where Endoscopy was not conclusive–Three case reports. (TAJ: Journal of Teachers Association, 2018)
Tranabdominal sonography along with USG guided FNAC can effectively evaluate the case of gastric carcinoma; while conventional endoscopy of upper gastrointestinal tract or Barium meal X-ray may not diagnose that case coclusively. Moreover, tranabdominal sonography is comparatively more cost effective and has also no radiation effect. From this perspective, this study highlights three case reports where endoscopy of upper gastrointestinal tract could not conclude the diagnosis but tranabdominal sonography along with USG guided FNAC could delineate the condition conclusively-which were later confirmed by histopathological examination.TAJ 2013; 26: 98-102